Socioeconomic disparities and infancy growth trajectory: a population-based and longitudinal study - Zi-yu Shao; Peng Wang; Pei Li; Yu Sun; Pei-pei Li; Peng Zhu (BMC, 2021)
Abstract Background The association of low socioeconomic status (SES) with childhood and adolescent obesity has been reported. It is unknown whether low SES affects body mass index (BMI) growth trajectory in the first 12 mo of life. Moreover, accelerated growth as a compensatory mechanism for low birth weight (LBW) during infancy, is an important predictor of later obesity. The aim of the present study was to examine the association of low SES with infancy BMI growth rate and trajectory for LBW and normal birth weight (NBW) infants. Methods From September 2012 to October 2014, a total of 387 infants in this longitudinal study was subjected to repeated measures of weight and length from birth to 12 mo in Hefei. Generalized growth mixture modeling was used to classify the infancy BMI growth trajectories. Differences in infancy BMI z score (zBMI) and BMI growth rate between low SES and high SES were estimated based on linear regression after adjusting for several confounders including maternal age, pregnancy BMI, physical activity during pregnancy, paternal BMI as well as alcohol use, paternal smoking status, breastfeeding duration and delivery mode. Results Infancy BMI trajectories in this study were classified into three categories: rapid growth (class 1), normal growth (class 2) and slow growth (class 3). Low SES infants had the higher zBMI than high SES infants for LBW group at age 6 mo [zBMI difference with 95% CI at 6 mo: 0.28(0.03, 0.53); at 12 mo: 0.21(0.01, 0.43)]. Low SES infants had more rapid zBMI growth rate than those with high SES for low birth weight between 0 and 6 months. Controlling for the confounders, these associations remained robust. We found the lower SES in the rapid growth group. Conclusions These findings highlighted the impact of low SES on increasing BMI and accelerated growth during early infancy. Health care and relatively optimal family environment in the first 12 mo of life, especially for LBW infants, are benefit to shape the better infancy growth trajectory.